О слове “байка” в говорах на территории Литовской ССР - Сивицкене, М. (Kalbotyra, 1972)
The article presents a description of the meanings and usage of the word baika and its variants baiki, baikis, baikos, baikė, baike, widely used in the dialects of Lithuanian Russians and Poles as well as in the dialects of the Lithuanian language. It is a Slavonic loanword, which having entered some dialects of Lithuanian seems to have penetrated in several meanings into the Russian dialects of Lithuania.Special attention is paid to the predicative functions of the word, when it acquires the mean ing of the adjective “not bad”, “fairly good” or the adverb “not badly”, “passably”, or is used to mean “it doesn’t matter”, “never mind”.cf. Iki mūsų kelias baika, o toliau blogas (Molėtai distr.). Dabar gyvenam baika (Ignalina distr.).Baikis, nueisi ir su tais batais (Skuodas distr.).Different meanings and syntactic functions of baika cover three areas, that differ in size and their boundaries are difficult to define.Polish dialects should be considered the source of the spread of the above-mentioned usage of baika.